Psychodrama with alcoholics : a social work perspective - Rabson, June Sara (Department of Social Development, 2023)
This thesis consists of a review of psychodrama literature, and an empirical application of the method in a psychotherapeutic context.' The literature review describes the classical psychodrama method, its history, techniques, associated and derivative methods. The descriptive part of the study also reviews applications of psychodrama, sociodrama, and role playing relevant to social work training and practice, with special reference to the field of alcoholism treatment.· The empirical study compares the use of psychodrama and role playing with inpatients receiving treatment in an alcoholism programme.